BASIC SCIENCE TEACHERS’ POSSESSION OF SCIENCE PROCESS SKILLS - Chiamaka N. Oguejiofor; Ebele C. Okigbo (Annals of the University of Craiova for Journalism, Communication and Management)
This research explored the possession of Science Process Skills (SPS) by basic science teachers as a perspective from Nigeria as a function of gender, teaching experience and teaching qualification. Three research questions guided the study and three hypotheses were tested at 0.05 alpha level. Descriptive survey research design was used in the study. The population comprised 178 Basic Science Teachers in all the 266 public secondary schools in the six education zones of Anambra state. No sampling was done because it is small and manageable. The instrument used for data collection was Science Process Skill Test (SPST). The reliability of SPST was established using Kuder richardson formular 21 (KR21), which yielded coefficient of internal consistency of .89. Research questions were answered using mean and standard deviation while t-test and ANOVA was used to test the null hypotheses. The findings of the study showed that gender has significant influence in the possession of Science process skills. Surprisingly, it was found that the perception and social convention that males are stronger than females in science appears not to be the case among basic science teachers. It also showed that there was no significant difference in the possession of Science Process Skills based on teaching experience and teaching qualification. Therefore, it was concluded basic science teachers can possess SPS irrespective of their teaching experience and qualification and it is a matter of individual differences. It was recommended that the government, managers and administrators of education in Nigeria should create a forum that will bring these teachers together and provide them the opportunity to improve (periodic training) on Science Process skills. Employment of basic science teacher should be gender friendly.